Stress-dependent grain size evolution of nanocrystalline Ni-W and its impact on friction behavior. (October 2016) - Argibay, N.; Furnish, T.A.; Boyce, B.L.; Clark, B.G.; Chandross, M.
Abstract: The friction behavior of ultra-nanocrystalline Ni-W coatings was investigated. A critical stress threshold was identified below which friction remained low, and above which a time-dependent evolution toward higher friction behavior occurred. Founded on established plasticity models we propose a correlation between surface grain size and applied stress that can be used to predict the critical stress separating the two friction regimes. This interpretation of plasticity models suggests that macro-scale low and high friction regimes are respectively associated with the nano-scale mechanisms of grain boundary and dislocation-mediated plasticity. Graphical abstract: